Plasma-induced signatures reveal an extracellular milieu possessing an immunoregulatory bias in treatment-naive paediatric inflammatory bowel disease. (29th January 2016) - Gurram, B; Salzman, N H; Kaldunski, M L; Jia, S; Li, B U K; Stephens, M; Sood, M R; Hessner, M J
Summary: The inflammatory state associated with Crohn's disease (CD) and ulcerative colitis (UC) remains incompletely defined. To understand more clearly the extracellular milieu associated with inflammatory bowel disease (IBD), we employed a bioassay whereby plasma of treatment naive paediatric IBD patients ( n = 22 CD, n = 15 UC) and unrelated healthy controls (uHC, n = 10) were used to induce transcriptional responses in a healthy leucocyte population. After culture, gene expression was measured comprehensively with microarrays and analysed. Relative to uHC, plasma of CD and UC patients induced distinct responses consisting, respectively, of 985 and 895 regulated transcripts [|log2 ratio| ≥ 0·5 (1·4-fold); false discovery rates (FDR) ≤ 0·01]. The CD:uHC and UC:uHC signatures shared a non-random, commonly regulated, intersection of 656 transcripts (χ 2 = P < 0·001) and were highly correlative [Pearson's correlation coefficient = 0·96, 95% confidence interval (CI) = 0.96, 0.97]. Despite sharing common genetic susceptibility loci, the IBD signature correlated negatively with that driven by plasma of type 1 diabetes (T1D) patients (Pearson's correlation coefficient = –0·51). Ontological analyses revealed the presence of an immunoregulatory plasma milieu in IBD, as transcripts for cytokines/chemokines, receptors and signalling molecules consistent with immune activation were under-expressed relative to uHC and T1D plasma. Multiplex enzyme-linked immunosorbent assay (ELISA) and receptor blockade studies confirmed transforming growth factor (TGF)-β and interleukin (IL)-10 as contributors to the IBD signature. Analysis of CD patient signatures detected a subset of transcripts associated with responsiveness to 6-mercaptopurine treatment. Through plasma-induced signature analysis, we have defined a unique, partially TGF-β/IL-10-dependent immunoregulatory signature associated with IBD that may prove useful in predicting therapeutic responsiveness.